How do match location and opponent level influence complex I offensive strategy in men's volleyball? The case of the Brazilian Men's Superleague - do Nascimento, M. H.; Laporta, L.; Vieira, P. H. C.; Rodrigues, M. C. J.; Rocha, A. C. R.; Rangel, C. C.; Freire, A. B.; Guimarães, J. D. S.; Pedrosa, G. F.; Ugrinowitsch, H.; Costa, G. D. C. T. (Journal of Human Sport & Exercise, 2025)
Match analysis identifies patterns in both defensive and offensive systems and key performance parameters, which should be applied in the practice context. This study examined the offensive game patterns in high-level Brazilian men's volleyball, considering the opponent`s ranking and match location. The sample comprised twenty-two matches involving the top four teams competing against each of the twelve participants in the 2021/2022 Brazilian Men's Volleyball Superliga. Each team played both home and away matches, leading to an analysis of 1,699 Complex I attack actions. The results indicated that the highest eigenvector centrality values were observed for settings primarily directed to positions 3 and 4, regardless of the opponent. Attacks were typically executed by the middle blocker positioned in front of and near the setter against single blocks, frequently resulting in points. Variations were observed depending on the team`s rotation and the set phase. High-level Brazilian volleyball teams exhibited minimal variations in their Complex I offensive strategies. However, finalist teams demonstrated differences in the distribution and attack patterns of the middle blocker.